USING THE SAVI LEARNING MODEL BASED ON GOOGLE CLASSROOM MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES IN SOCIOLOGY IN CLASS XI IPS 2 SMAN 2 SELONG - Rizian Asri; Ni Made Novi Suryanti; Nursaptini Nursaptini (PROGRES PENDIDIKAN, 2023)
Sociology is one of the subjects taught at the high school level which currently uses the 2013 curriculum, in implementing the 2013 curriculum a model and a media are needed whose learning is student-centered so that students are required to be active and innovative in learning, but in the implementation of the national curriculum in class XI IPS 2 SMAN 2 SELONG students are still fine it is difficult to play an active role in learning so that student learning outcomes are low, this is because the learning models and media used are still traditional. Low student learning outcomes are the background for this research. The purpose of this study is to improve student learning outcomes in class XI IPS 2 SMAN 2 SELONG. This research was conducted in 2 cycles as a class action research project. The data in this study were collected by observing, reflecting, learning achievement tests, and documentation. The results of this study showed that the percentage of learning implementation was 66.6% and the percentage of student learning outcomes was 66.6% in chicle I, then there was an increase after the implementation of cycle II with the percentage of learning implementation being 90.4% and the percentage of student learning outcomes being 84.8%.